PARADIGMA BARU KEBIJAKAN STANDAR NASIONAL PENDIDIKAN SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN INDONESIA - Sulistiyanto, Eko; Masrokan, Prim; Muhajir, Asâ€™aril (Kelola: Journal of Islamic Education Management, 2023)
Â The government has issued and evaluated various policies to improve the quality of Indonesian Education. This study aims to analyze various policies and new paradigms of policies related to National Education Standards. The method used in this research is a literature study. The results of the study show that there is a paradigm shift related to policies regarding National Education Standards from those oriented to content standards, then shifted to graduate Competency Standards as an effort to improve the quality of Indonesian education.